Pengaruh Kualitas Pelayanan dan Store Atmosphere terhadap Kepuasan Konsumen : Survei pada Konsumen Imah Kopi Mamang BRP Kota Taikmalaya - Taftasani , Muhammad (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
This study aims to determine the simultaneous and partial effect of service quality and store atmosphere on consumer satisfaction of Imah Kopi Mamang. The research method used in this research is quantitative research with causality method and survey approach. The population studied were 100 respondents. The data collected in the form of primary data and secondary data. Data analysis in this study used multiple linear regression analysis using SPSS version 24 software. The results showed that service quality and store atmosphere simultaneously had a significant effect on consumer satisfaction at Imah Kopi Mamang. Quality of service, partially has a significant effect on consumer satisfaction Imah Kopi Mamang. Store atmosphere, partially significant effect on consumer satisfaction Imah Kopi Mamang.